Case Report: A fatal case of CNS actinomycosis mimicking Tolosa–Hunt syndrome: Is it time to reevaluate diagnostic criteria? - Bristol, Natalie; Venegas, Courtney; Snehal, Isha; Maisenbacher, Mathias; Higgins, Ryan; Auen, Thomas; Cichon, Catherine; Hankins, Richard; Barnes, Christie; Cathcart, Sahara; Yuil-Valdes, Ana; Chen, Jie; et al. (Frontiers in Medicine, 2025)
BackgroundTolosa-Hunt Syndrome (THS) is a rare diagnosis characterized by headaches, painful ophthalmoplegia, and granulomatous inflammation of the cavernous sinus. It is a diagnosis of exclusion but can mimic many other conditions, including central nervous system (CNS) actinomycosis. This systematic review evaluated the frequency of CNS actinomycosis initially diagnosed as THS and evaluated lapses in the current diagnostic criteria which were related to poor outcomes.Case reportWe present a case of a 43-year-old man who was diagnosed with THS 10 weeks prior to his final hospital presentation. Previous infectious work up was negative. He returned with altered mental status and was found to have leptomeningeal enhancement, vasculitis, and acute infarcts. He decompensated while on broad-spectrum antimicrobials. The patient was ultimately found to have CNS actinomycosis when next generation sequencing identified Actinomyces israelii. This diagnosis was confirmed by biopsy. Unfortunately, due to the extent of the infarcts, the patient passed away.ResultsA total of 344 records were analyzed for title/abstract review and ultimately revealed Eight cases of CNS actinomycosis initially diagnosed as THS. 62.5% of cases had dental history prior to symptom onset. Cerebral spinal fluid cultures were obtained in 75% percent of cases, and all were negative for Actinomyces. 88% of cases were diagnosed by histopathology evaluation and 25% of cases were fatal.ConclusionWith the low reported prevalence of CNS actinomycosis, the inadequacy of current testing for Actinomyces, and the significant overlap of symptoms with THS, it is essential that clinicians are aware of CNS actinomycosis as a potential infectious etiology if early and potentially curative treatment is to be provided. The current definition of THS may encourage harmful practices and should be revised.